2022
DOI: 10.3390/ijms232415762
|View full text |Cite
|
Sign up to set email alerts
|

The Role of rs713041 Glutathione Peroxidase 4 (GPX4) Single Nucleotide Polymorphism on Disease Susceptibility in Humans: A Systematic Review and Meta-Analysis

Abstract: Aim: The single-nucleotide polymorphism (SNP) rs713041, located in the regulatory region, is required to incorporate selenium into the selenoprotein glutathione peroxidase 4 (GPX4) and has been found to have functional consequences. This systematic review aimed to conduct a meta-analysis to determine whether there is an association between GPX4 (rs713041) SNP and the risk of diseases in humans and its correlation with selenium status. Material and methods: A systematic search for English-language manuscripts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…Some selenoproteins have been investigated in this regard due to altered levels in cancers compared to normal tissues, their molecular function, or the association of genetic variations in the corresponding genes to cancer risk or outcome [ 25 , 26 ]. For example, polymorphisms in the genes for members of the glutathione peroxidase family of antioxidant selenoproteins have been associated with the risk of several cancers, although epidemiological studies have often resulted in conflicting results [ 27 , 28 ]. Possible reasons for studies yielding different conclusions include the impact of selenium status or ethnicity of study participants [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some selenoproteins have been investigated in this regard due to altered levels in cancers compared to normal tissues, their molecular function, or the association of genetic variations in the corresponding genes to cancer risk or outcome [ 25 , 26 ]. For example, polymorphisms in the genes for members of the glutathione peroxidase family of antioxidant selenoproteins have been associated with the risk of several cancers, although epidemiological studies have often resulted in conflicting results [ 27 , 28 ]. Possible reasons for studies yielding different conclusions include the impact of selenium status or ethnicity of study participants [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study reported no significant overall association with colorectal adenoma risk for GPX4 ( Peters et al, 2008 ). However, a recent systematic review showed that carriers of the GPX4 (rs173041) T allele were associated with an increased risk of developing colorectal cancer ( Barbosa et al, 2022 ). Another most recent study reports that high expression of GPX4, which suppresses ferroptosis, was associated with poorer 5-year overall survival only in KRAS mutant tumors from male colorectal cancer patients ( Yan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, exhausting the glutathione levels would decrease GPX4 activity and intensify its propensity for ferroptosis [ 17 ] ( Figure 1 ). Glutathione peroxidase 4, also known as phospholipid hydroperoxide glutathione peroxidase (GPX4), possesses a unique capability to reduce hydroperoxides found in intricate lipids like phospholipids, cholesterol, and cholesterolester hydroperoxides, even when they are incorporated into biomembranes or lipoproteins [ 18 ]. This ability is crucial for preventing the iron (Fe 2+ )-dependent formation of harmful lipid reactive oxygen species (ROS) [ 18 ].…”
Section: Introduction To Ferroptosismentioning
confidence: 99%
“…Glutathione peroxidase 4, also known as phospholipid hydroperoxide glutathione peroxidase (GPX4), possesses a unique capability to reduce hydroperoxides found in intricate lipids like phospholipids, cholesterol, and cholesterolester hydroperoxides, even when they are incorporated into biomembranes or lipoproteins [ 18 ]. This ability is crucial for preventing the iron (Fe 2+ )-dependent formation of harmful lipid reactive oxygen species (ROS) [ 18 ]. The significance of GPX4 extends to normal physiology, as its absence is incompatible with life due to its pivotal role in preserving mitochondrial function, inflammation, differentiation, immunity, and cell death [ 18 ].…”
Section: Introduction To Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation